Maestría en seguridad Industrial mención en Prevención de Riesgos y Salud Ocupacional - Almeida Villena., Gerardo Ramiro (2017)
Personal protective equipment (P.P.E.) for topography personnel now differs from normal work equipment; this is because topography personnel develop their full working day in the fíeld, with strong walks. For this reason, the personal protective equipment must be focused to give comfort to the worker in any weather or terrain. Prior to the application of this research, topography personnel rejected to use the standard construction equipment, they preferred to wear clothing that would allow more freedom of movement in the fíeld, here cause of the problem.This issue has allowed us to solve the problem of improper use of equipment, with the acceptance of our ergonomic protection equipment. When we got implementing an ergonomic personal protective equipment for extemal use and different climates, we got improving the daily performance of workers, this PPE reduce fatigue in their daily work hours, representing an improvement in quality and production for the company. The investment of this personal protective equipment that improves the worker's quality and safety, through years represents a self-sustaining investment because it improves the performance and it reduce the periods of recovery of energy and comfort in the workers. The application of this theme represents a benefít in the worker - company relationship with positive results respectively.